Construction and Evaluation of Recombinant Pseudorabies Virus Expressing African Swine Fever Virus Antigen Genes - Chen, Liyi; Zhang, Xinheng; Shao, Guanming; Shao, Yangyang; Hu, Zezhong; Feng, Keyu; Xie, Zi; Li, Hongxin; Chen, Weiguo; Lin, Wencheng; Yuan, Hengxing; Wang, Hailong; et al. (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly contact infectious disease caused by the African swine fever virus (ASFV). The extremely complex structure and infection mechanism make it difficult to control the spread of ASFV and develop the vaccine. The ASFV genome is huge with many antigenic genes. Among them, CP204L (p30), CP530R (pp62), E183L (p54), B646L (p72), and EP402R (CD2v) are involved in the process of the virus cycle, with strong immunogenicity and the ability to induce the body to produce neutralizing antibodies. In this study, the recombinant virus rBartha-K61-pASFV that expresses the above ASFV antigen genes was constructed by Red/ET recombineering technology using pseudorabies virus (PRV) vaccine strain Bartha-K61. Western blot analysis showed that the ASFV antigen gene was expressed and the recombinant virus showed good genetic stability and proliferation characteristics in 15 continuous generations on porcine kidney (PK15) cells. The results of immunoassay of piglets and mice showed that rBartha-K61-pASFV had good immunogenicity and could induce higher antibody levels in the body. Therefore, PRV was a promising viral vector for expressing the ASFV antigen gene, and all the experiments in this study laid a foundation for the further development of a new viral vector vaccine of ASFV.